2017
DOI: 10.4103/ajm.ajm_76_17
|View full text |Cite
|
Sign up to set email alerts
|

Muslim patients in Ramadan: A review for primary care physicians

Abstract: Fasting Ramadan, in which Muslims abstain from specific habits and behaviors from dawn to sunset, is one of the five Pillars of Islam. While there are several exemptions from fasting, many Muslim patients with acute or chronic medical conditions still choose to fast, which may adversely affect their health if not addressed properly. Some patients may not be well educated about the effects of some medical treatments and procedures on the validity of their fast, which can unnecessarily lead to suboptimal managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 25 publications
1
52
0
Order By: Relevance
“…Independentsamples t-test was applied for homogeneity of general characteristics, anthropometric measurements, and dietary intakes in two groups. We used paired samples t-test to assess the effects of barely bread and wheat 1 Body mass index The results showed that rate of hunger before Iftar in the barley bread group is significantly lower than wheat bread group (P value<0.001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Independentsamples t-test was applied for homogeneity of general characteristics, anthropometric measurements, and dietary intakes in two groups. We used paired samples t-test to assess the effects of barely bread and wheat 1 Body mass index The results showed that rate of hunger before Iftar in the barley bread group is significantly lower than wheat bread group (P value<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Fasting is one of the main worships of Islam which healthy able Muslims abstain from drinking, eating, medications and smoking during the day [1]. Fasting begins after Sahur, a meal before sunrise, and is completed after Iftar, another meal after sunset which usually begins with consuming dates or sweetened water and followed by other foods [2].…”
Section: Introductionmentioning
confidence: 99%
“…Most Muslims are passionate about fasting during this month, although sick people are exempted. However, many diabetics may not perceive themselves as sick and a high proportion fasts [5][6]. A large epidemiology study of Muslims with diabetes in 13 Islamic countries -the Epidemiology of Diabetes and Ramadan (EPIDAR) study -showed 43% of patients with type 1 and 79% of those with type 2 diabetes fasting during Ramadan [7].…”
Section: Introductionmentioning
confidence: 99%
“…According to Islamic calendar (Hijra), each year Ramadan comes about 10 days earlier thus, occurring at various times in different seasons in a 33-year cycle. 1 One of the fundamentals of fasting is totally refraining oneself from consuming any food or drink during the fasting hours. Although traditions may vary according to geographical location, customs are generally influenced by religion specially in regions like middle east and southeast Asia.…”
Section: Introductionmentioning
confidence: 99%